Patients’ expectations with regard to the quality of orthopedic medical care - Marcon, Lucas Antônio Ferraz; Moura, Bruno Arnaldo Bonacin; Silva, João Luiz Vieira da; Souza, Eduardo Dias de; Buss, Eduardo Hubbe (Journal of the Foot & Ankle, 2020)
Objective: To assess, through the Surgical and Medical Experience Questionnaire translated and adapted into Portuguese, the opinions and expectations of patients with regard to the treatment protocols and medical training of the foot and ankle orthopedic specialist. Methods: This cross-sectional observational study assessed, through the application of a questionnaire, the opinions and expectations of patients with regard to orthopedic protocols adopted by the foot and ankle specialist. Results: One hundred and thirty patients were selected. Among the participants, 33.8% were male and 66.2% female. The predominant characteristics of a good physician were good outcomes, according to 31% of the participants, followed by quality of care according to 28.6%, and qualities of a good surgeon, chosen by 27.6%. Approximately 89% of patients do not conduct any research on their physician. Correlation was found between the study level and the choice of physician. Conclusion: The demand for physicians with highly specialized skills has increased over the years. It is evident that in the case of better educated patients, a physician’s resume is much more important, unlike less educated patients. It is possible to observe that, for patients, there are still multiple barriers and variables. Level of Evidence V, Therapeutic Study; Expert Opinion.